Conceptualization of interdisciplinary creative engineering activities - Anton V. Ivaschenko; Oleg K. Golovnin; Anna I. Demina (Семиотические исследования)
In the context of the development of generative artificial intelligence technologies, the article raises the question of whether it is sufficient to reproduce the methods of human meaning generation for inventive creative activity. It is shown that the answer to this question depends on the understanding and representation of the result of creative activity. The result of creative activity should be presented in a specific language, and this language becomes sufficient for presenting the invention as a result of engineering activity. In the course of reasoning, we turn to semiotics, the task of which in this case is to select linguistic methods for representing the results of engineering creativity, rules and constructions that are effective for the development of generative artificial intelligence and suitable for human interpretation. A concept is proposed that assumes that a specific technical means of the genesis of semiosis of engineering creativity should be singled out as a semiotic basis for intellectual engineering. To create such a means, it is necessary to additionally implement software services for stimulating inventive activity, containing concepts of existing solutions to engineering problems for conveying the accumulated experience. Inheriting specific cases of engineering problems from these concepts, it is possible to construct a sufficiently branched tree of solutions, the intersection of whose branches contributes to the emergence of the semiosis of engineering creativity as the neural substrate of the language of intellectual invention. The application of the proposed concept in practice can become the organizational basis for the implementation of artificial intelligence capable of technical creativity.